Circadian rhythms of saliva melatonin in ADHD, anxious and normal children - Paclt, Ivo; Ptácek, Radek; Kuzelová, Hana; Cermáková, Nikol; Trefilová, Alexandra; Kollárová, Patricie; Cálková, Tereza; Csemy, Ladislav; Cíhal, Libor (Neuro endocrinology letters, 2011)
BACKGROUND: Attention-deficit/hyperactivity disorder (ADHD) and anxiety disorders are the most frequent psychiatric disorders in children. Changes in rhythms of symptoms during the day may be influenced by genetic, biological and psychological factors. Some changes of melatonin rhythm may hypothetically change the activity of ADHD by changing arousal or in anxiety children by changing their emotional state. In our present study we identify one group of ADHD children combine type without comorbids, one group of anxiety children and a control group. Most changes of melatonin daily rhythm are supposed in the anxiety group, especially in sleeping time, and more prominent change in the ADHD group with prominent hyperactivity and conduct disorder symptoms. METHODS: Thirty-four ADHD and forty-three control children and eleven anxiety children, all 6-12 years old, participated in the study. The saliva specimens were collected in four different sessions during the school year, around the time of the spring and autumn equinox, when the natural light lasted 11.2 h ± 0.9 h. RESULTS AND CONCLUSIONS: In our study more symptoms of conduct disorder elevated positive or negative correlations between psychopathology and saliva level of melatonin in ADHD and anxiety samples. We hypothesize that co-morbidity of ADHD or anxiety with impulsivity and conduct disorders might have elevated correlations between psychopathology of ADHD or anxiety and plasma melatonin level.
Keywords: sliny; Child; Saliva; hyperkinetická porucha; Circadian Rhythm; Anxiety Disorders; Attention Deficit Disorder with Hyperactivity; cirkadiánní rytmus; Humans; lidé; úzkostné poruchy; dítě; melatonin; Melatonin